RA07.03: NON-ENDOSCOPIC SCREENING FOR ESOPHAGEAL SQUAMOUS CELL CARCINOMA: INTERIM ANALYSIS. (14th September 2018) - Bhatt, Maunil; Shah, Parth; Gandhi, Fenil; Patel, Parth; Patel, Dhwani; Patel, Deep; Parmar, Vipal; Mehta, Bhavna; Rajput, Sanjay; Godfrey, Tony; Litle, Virginia
Abstract: Background: Esophageal Squamous Cell Carcinoma(ESCC) comprises 90% of esophageal cancer worldwide which typically presents at advanced stages and has extremely poor outcomes. Established risk factors for ESCC include tobacco, alcohol and betel nut use. We hypothesized that a screening program for high risk subjects could be established in a low- to middle-income country, using a low-cost, non-endoscopic, retrievable capsule sponge device called EsophaCap(EC). Methods: The Institutional Review Board-approved study was conducted in western India from March 2017 through February 2018. Patients with high risk characteristics(smoking, tobacco, betel nut, alcohol, hot beverage consumption) were included. Patients with severe dysphagia, current upper aerodigestive tract cancer, metastatic cancer, esophageal varices, cirrhosis, and portal hypertension were excluded. Following EC specimen retrieval, endoscopic biopsies were collected at 20cm, 30cm and from any visible mucosal abnormalities. Cytology and biopsy specimens underwent H&E staining. An interim analysis was performed to make necessary changes given the lack of baseline data in this field. Results: Of the 100 enrolled subjects(85% males, median age 50 years), 93% successfully swallowed the EC and 90% completed endoscopy. The median patient experience score on a 6-point visual analog scale was 5('minimal discomfort'). Six(7%) subjects had ESCC on their biopsy. In 2 ESCC patients with mild dysphagia, sponge cytology accurately detected atypical squamous cells(ASC) and dysplasia(100% Sensitivity & Specificity). The other 4 ESCC patients had moderate dysphagia with a near-complete obstruction. In 2 asymptomatic patients with no mucosal abnormalities on endoscopy or biopsies, sponge cytology detected ASC. Longitudinal follow-up of these patients is ongoing. On biopsies from twenty-one(23%) patients, leukoplakia was identified. Conclusion: ESCC screening using the EC is feasible with good patient tolerance. Analysis of the cytology samples with H&E staining is potentially accurate for patients with non-obstructive lesions but has a high false negative rate in patients with advanced lesions, when the EC can't traverse the obstruction. An unusually high rate of leukoplakia was detected in this population and will be evaluated as a potentially pre-malignant lesion with increased risk for development of ESCC. Future studies will include high-throughput sequencing to identify molecular changes that may correspond with leukoplakia or dysplastic cells retrieved with the EC. Disclosure: All authors have declared no conflicts of interest.